Simultaneous Detection of Cu2+ and Hg2+ via Two Mutually Independent Sensing Pathways of Biimidazole Push-Pull Dye - Dey, Nilanjan; Kulhánek, Jiří; Bureš, Filip; Bhattacharya, Santanu (American Chemical Society, 2019)
An easy-to-synthesize, biimidazole push-pull dye has been designed, comprising two mutually independent analyte binding sites. It has been found that Hg2+ coordinates with the compound via thiophene residue and inhibits the charge-transfer (CT) process, which transforms the yellow-colored solution colorless. On the other hand, an unusually large bathochromic shift is observed in CT band upon addition of Cu2+, accompanied by a change in the color from yellow to red. A rather surprising observation is made from mechanistic studies, where it indicates that Cu2+ catalyzes the formation of 6-imino-5,6-dihydropyrrolo[3,4-d]imidazole-4(3H)-one (IPIMO) derivative. This strongly affects the charge-transfer state of the compound as well as its polarizability. Most importantly, this is the first report where IPIMO formation reaction has been exploited for sensing of a metal ion. Further, the system was employed for screening of both of these metal ions in wastewater samples. Recovery values ranging from 93.3 to 105.0% confirm the suitability of the present method for estimating trace level of metal ions in complex matrices. In addition, inexpensive on-site detection systems were developed using paper strips.
Simultánní detekce Cu2 + a Hg2 + pomocí dvou vzájemně nezávislých snímacích cest biimidazolového push-pull barviva
Keywords: fluorescent-probes; biological-fluids; selective detection; metal ions; phthalocyanines; sensors; samples; copper; water; coordination; fluorescentní sonda; selektivní detekce; ftalocyaniny; sensory; měď; voda; koordinace